Latent tuberculosis coinfection in mild COVID-19 is associated with a distinct immune cell phenotype marked by enhanced cytotoxic degranulation and mitochondrial alterations - Peña-Bates, Carlos; Ramón-Luing, Lucero A.; Flores-Gonzalez, Julio; Espinosa, Enrique; Martinez-Moreno, María F.; Medina-Quero, Karen; Vargas-Hernandez, Marco A.; Téllez-Navarrete, Norma A.; Sosa-Gomez, Fernando M.; Becerril-Vargas, Eduardo; Salazar, Miguel Ángel; Chavez-Galan, Leslie (Frontiers in Immunology, 2025)
IntroductionThe chronic nature of latent tuberculosis infection (LTBI) allows it to coexist with diverse pathologies. However, it remains unclear whether immune alterations associated with LTBI influence COVID-19 coinfection and patient outcomes. This study aims to compare the immune phenotype of patients with LTBI/COVID-19 to those with COVID-19 alone, in order to assess whether latent tuberculosis infection induces significant immune cell alterations.MethodsPeripheral blood mononuclear cells were cultured and stimulated with the SARS-CoV-2 Spike protein and Mycobacterium bovis Bacillus Calmette-Guérin (M. bovis BCG) to evaluate cellular distribution and function.Resultsthe LTBI/COVID-19 group exhibited a narrower range of symptoms and required less complex treatment regimens than the COVID-19 group. The cellular evaluation revealed that individuals with COVID-19 displayed a distinct immune profile, characterized by a predominance of monocytes expressing pro-inflammatory and regulatory markers, including TNFR2, HLA-DR+TNFR2, and CD71. While CD4+ T cell subpopulation distribution and function were similar across groups, LTBI/COVID-19 and COVID-19 exhibited similar frequencies of CD8+perforin+ and CD8+Granzime B+ T cells. However, LTBI/COVID-19 displays lower soluble levels of granzyme B and perforin in culture supernatants and perforin, granulysin, and sFas in plasma compared to COVID-19. Notably, CD8+ T cells from LTBI/COVID-19 showed higher antigen-specific degranulation than COVID-19. Moreover, LTBI/COVID-19 individuals predominantly displayed CD4+ and CD8+ T cells with highly polarized, compact mitochondria at baseline, which remained unchanged under stimulation. In contrast, COVID-19 had T cells with highly polarized, fragmented mitochondria at baseline, a profile that persisted under stimulation.ConclusionThe findings reveal significant alterations in monocytes and T cells of individuals with LTBI/COVID-19, suggesting that co-infection may induce changes in the cellular phenotype and cytotoxic function of CD8 T cells.